Big Steel, Invention, and Innovation: Reply - Adams, Walter; Dirlam, Joel B. (Quarterly Journal of Economics, 1967)
I. The invention, 475. — II. The innovation: domestic lag, 475. — III. The innovation: international lag, 476. — IV. Explanation of the lag, 478. — V. Conclusion, 481.